PSVIII-B-4 Differences in Bull Prolificacy and Offspring Body Performance in Western Canadian Multi-Sire Commercial Herds. (21st September 2022) - Oyedeji, Oluwatobi; Thompson, Sean; Doherty, Becky; Rogerson, Jessica; Hamilton, Bevin; Durunna, Obioha N
Abstract: Beef cattle producers employing multi-sire natural mating systems expect superior breeding and production performance from the bulls. The bulls that sire more healthy calves are more economical considering that the annual maintenance cost for each bull could exceed 2000. Industry benchmarks on bull prolificacy and the production performance of their offspring will enable producers to make better selection and culling decisions. This 3-yr study evaluated 2, 130 calves from 62 bulls and 1, 869 cows to assess bull prolificacy and calf production performance in multi-sire breeding pastures – VS (VS1, VS2), OS, CF, KF, DIF, and DEF across Alberta Canada. Calves were matched to bulls using DNA paternity analysis. Prolificacy was assessed among bulls engaged in breeding activities year-over-year. Percentage calves assigned to each sire from sire-progeny matches were assessed within sites over consecutive years (VS1: 11.5 - 46.34%, VS2: 4 - 75%, OS: 2 - 17%, CF: 6 - 33%, KF: 5 - 38%, DIF: 3 - 26%, DEF: 16 - 62%). The differences in body and growth performance of calves were analyzed with linear mixed models. The average birth weight of calves varied by sires (p < 0.05) in VS1 (39.92kg – 42.74kg; P < 0.05), OS (34.09kg–39.49kg), CF (35.72-40.27kg) but not in VS2 (36.35 – 38.02kg; P > 0.05). Similarly, the average calf weaning weights among sires did not differ in VS1 (309.44 – 316.77kg; P = 0.33) but were different (P < 0.05) in OS (219.25 - 236.36kg), CF (216 -243 kg) and KF (178 - 232kg). Differences were also observed in calves' average daily body gain among sires in VS1 (0.93 – 1.14 kg d -1 ; P < 0.0001). Verifying the sires of calves in multi-sire herds will enable beef producers to make effective management and economic decisions. Measuring the production performance of calves from different bulls is important for the beef industry's profitability and sustainability.